Application of floating treatment wetlands for stormwater runoff: A critical review of the recent developments with emphasis on heavy metals and nutrient removal - Sharma, Rozi; Vymazal, Jan; Malaviya, Piyush (The Science of the total environment, 2021)
Floating treatment wetlands (FTWs) are increasingly gaining popularity due to a set of valuable features like wastewater remediation under varied conditions, ecosystem quality preservation, landscape conservation, and aesthetic benefits. FTW is a phyto-technology in which macrophytes grow on a floating raft with their roots in permanent contact with water and remove pollutants via several physicochemical-biological processes. FTW is highly capable of overcoming technical and operational challenges that come way in stormwater treatment due to the erratic nature of hydrologic and input pollutant loads because this innovative buoyant hydroponic design can move up and down with fluctuating water levels in the stormwater pond and can treat highly variable flows. Plants and biofilms attached to the roots hanging beneath the floating mat play a pivotal role in FTWs. The present review encompasses the concept of FTWs, their structural designs, relevance in stormwater management, and mechanism of plant uptake for pollutant removal. The role of FTWs to remove heavy metals and nutrients is also critically analyzed. Understanding hydraulics and other parameters of FTW is vital to effective design. Hence, the role of vegetation coverage, vegetation type, sorption media, aeration frequency, and intensity, and plant density to enhance system efficiency is also highlighted. Due to their operational flexibility and environmentally friendly working with no additional burden on existing urban land use, FTWs entice broad international interest and offer a coherent solution for stormwater management. MAIN FINDINGS: The review delivers state-of-the-art analysis of the current understanding of hydraulics and other parameters of FTWs, and associated mechanisms to enhance the treatment efficiency of FTWs for nutrients and heavy metals removal.
Keywords: Heavy metal; Plant; odpad tekutý - odstraňování; chemické látky znečišťující vodu; Water Pollutants, Chemical; čištění vody; mokřady; Waste Disposal, Fluid; déšť; Constructed wetland; zásobování vodou; Rain; Nutrients; Wetlands; živiny; Water Purification; těžké kovy; Water pollution; ekosystém; Ecosystem; Water Supply; Remediation; Metals, Heavy; Stormwater